Supramolecular assembly induced chiral interface for electrochemical recognition of tryptophan enantiomers. Issue 17 (12th April 2021) - Sun, Yi-Xin; Zhang, Dan-Dan; Sheng, Yang; Xu, Defeng; Zhang, Rong; Bradley, Mark
Abstract : The β-CD@PEI-Fc chiral interface was prepared based on the supramolecular host–guest interaction between ferrocene (Fc) grafted polyethyleneimine (PEI-Fc) and chiral β-cyclodextrin (β-CD). Abstract : The β-CD@PEI-Fc chiral interface was prepared based on the supramolecular host–guest interaction between ferrocene (Fc) grafted polyethyleneimine (PEI-Fc) and chiral β-cyclodextrin (β-CD). SEM results show that β-CD@PEI-Fc interface has a regular spatial structure, which can effectively distinguish tryptophan (Trp) enantiomers. Under the optimal conditions, differential pulse voltammetry shows that the peak current ratio ( I d / I l ) of Trp enantiomers can reach 2.84 at 15 °C. More interestingly, the β-CD@PEI-Fc/GCE exhibited chiral recognition of d -Trp and l -Trp via water contact angle measurements. There was a good linear relationship between the peak current and the concentration of Trp enantiomers in the range from 0.005 mM to 0.10 mM. Finally, the chiral interface can be applied for quick detection of the proportion of isomers in Trp racemic solution, which is very important for chiral recognition in racemic mixture of chiral compounds. Meanwhile, the β-CD@PEI-Fc/GCE showed good stability and reproducibility.